Screening of sugar alcohols and their binary eutectic mixtures as phase change materials for low-to-medium temperature thermal energy storage. (Ⅱ): Isothermal melting and crystallization behaviors. (1st August 2019) - Shao, Xue-Feng; Yang, Sheng; Wang, Chao; Yang, Yong-Jian; Wang, Wu-Jun; Zeng, Yi; Fan, Li-Wu
Abstract: Based on the non-isothermal phase change behaviors of twenty-one pure and mixture sugar alcohols presented in our previous study (Part Ⅰ), the isothermal melting and crystallization behaviors were further tested in this supplemental work for five selected pure sugar alcohols (xylitol, erythritol, d-mannitol, d-dulcitol and inositol) and their five binary eutectic mixtures to make an advanced screening of these candidates for low-to-medium temperature latent heat storage. The isothermal melting and crystallization behaviors of these ten candidates were tested at a constant degree of superheat (10 °C) and various degrees of subcooling up to 210 °C. The phase change temperatures, degrees of supercooling and durations of phase change were determined by the recorded temperature-history curves. It was found that the incrystallizable xylitol and its eutectic mixture of xylitol (75 mol%) + erythritol with low melting points under 100 °C are also unable to crystallize during isothermal cool-down at any degrees of subcooling (30–90 °C) due to the unavailability to nucleation. The rest eight crystallizable candidates all suffer from severe supercooling and are unable to crystallize at low degrees of subcooling (<20 °C). They undergo both one-phase supercooling due to poor nucleation performance and two-phase supercooling, which was unable to be obtained previously by non-isothermal cooling, due to slow crystallization kinetics. However, it seems difficult to find a correlation between the observed degrees of supercooling in both the liquid and solid phases and the prescribed degrees of subcooling by only three consecutive isothermal melting and crystallization cycles, as a result of the randomness of nucleation and large size of samples. The duration of crystallization was shown to decrease with increasing the degree of subcooling for both pure and mixture sugar alcohols due to the enhanced driving force for crystallization. The durations of crystallization of the mixture sugar alcohols appear to be longer than those of their pure compounds, due to the lower thermal conductivity and higher dynamic viscosity of the mixtures. Combining the present isothermal and the previous non-isothermal test results, it has been confirmed that the difficulty in crystallization and the severe supercooling are the primary issues for sugar alcohols, which must be addressed before they can be used in real-world latent heat storage systems. Highlights: Isothermal phase change behaviors were tested for pure and mixture sugar alcohols. Data concerning the phase change behaviors were analyzed via the T -history method. All candidates with a melting point below 100 °C were found to be incrystallizable. Crystallizable candidates were found to experience one- and two-phase supercooling. Both isothermal and non-isothermal tests confirmed the issues with crystallization.